THE ASSISTANCE IN DETERMINING BUSINESS LOCATIONS FOR SMES - Muhammad Iqbal Alamsyah; Anggono Raras Tirto Sakti; Astrin Kusumawardani (Inaba of Community Services Journal, 2022)
Small and medium-sized companies face many problems, one of which is intense competition in a dynamic environment. In 2019 the servant has completed research and compiled a location feasibility study that can be implemented by MSMEs, through market potential analysis and financial projections using a modified GE-Matrix mapping. The target partner for this community service is a coffee shop in Bandung which was founded in 2017, namely Holly Chopper Gallery and Coffee located in the Buah Batu area in Bandung City. The implementation method that will be carried out is to provide assistance with target partners and assist MSMEs in mapping out alternative locations to be chosen by entrepreneurs. Determining the right business location decision will have an impact on business sustainability, so the choice of location needs to be considered carefully. The output in the implementation of this community service is to increase the knowledge and skills of partners in determining the location of the business. In addition, community service is strived to be published in accredited national journals. In addition, other community service outputs are teaching materials for students, which can be studied and implemented in other MSMEs.